Socioeconomic Determinants of Undernutrition Among Children Under Five: Evidence from Southeast Sulawesi, Indonesia - Afdhal, Muh.; Wahyudin (Science Tech Group, 2026)
Southeast Sulawesi has a high prevalence of undernutrition in children under five (27.7%) in 2024. Socio-economic factors such as poverty and maternal education are suspected to influence this condition. This study aims to analyze the influence of poverty levels and maternal education (Mean Years of Schooling/MYS) on the prevalence of child undernutrition in 17 districts/cities in Southeast Sulawesi. Secondary data from the Central Statistics Agency (BPS) in 2024 were used, with 17 observations. Analysis was conducted using Negative Binomial Regression to address overdispersion. Independent variables were the percentage of the poor population and the MYS of women. The Negative Binomial Regression model was confirmed as the best fit. Maternal education had a significant negative effect on undernutrition cases (IRR = 0.688; p=0.012). The poverty level also showed a significant negative relationship (IRR = 0.863; p=0.034). Maternal education plays an important role in reducing the risk of undernutrition. The negative relationship between poverty and undernutrition indicates the presence of specific factors or intervention programs in Southeast Sulawesi that require further investigation.